The storm - Drake, David, 1945- (Drake, David, 1945- Time of heroes series., 2020)
"The universe has shattered into chaos and monsters. Jon, the Leader, is dedicating his life to reuniting the scattered hamlets into a Commonwealth where all humans can live protected against the darkness. But no man can reshape the universe by himself. Jon has Makers to build weapons and clerks to handle the business of government--but he also needs Champions to face the powers of chaos which will not listen to any argument but force. Lord Pal of Beune is one of those Champions. But now Guntram, the man who transformed Pal from an ignorant rube into a bulwark of the Commonwealth, has disappeared. Pal must locate his friend and mentor--and then battle an entity which may be at the core of the splintered universe"--